2008
DOI: 10.1523/jneurosci.5748-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neural Underpinnings of Gesture Discrimination in Patients with Limb Apraxia

Abstract: Limb apraxia (LA), is a neuropsychological syndrome characterized by difficulty in performing gestures and may therefore be an ideal model for investigating whether action execution deficits are causatively linked to deficits in action understanding. We tested 33 left brain-damaged patients and 8 right brain-damaged patients for the presence of the LA. Importantly, we also tested all the patients in an ad hoc developed gesture recognition task wherein an actor performs, either correctly or incorrectly, transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
173
4
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(196 citation statements)
references
References 70 publications
15
173
4
1
Order By: Relevance
“…This led to the classic model of "visuokinesthetic motor engrams," which guide the sequencing and timing of motor movements, that are localized to these inferior parietal regions (Heilman et al, 1982;Heilman and GonzalezRothi, 1993). A more recent voxel-based lesion-symptom mapping study in apraxic patients without aphasia suggested that the left inferior frontal gyrus rather than inferior parietal cortex is associated with deficits in gesture discrimination (Pazzaglia et al, 2008). Two lesion subtraction studies implicated a relatively extensive region containing inferior frontal as well inferior parietal cortex in gesture recognition (Tranel et al, 2003;Buxbaum et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This led to the classic model of "visuokinesthetic motor engrams," which guide the sequencing and timing of motor movements, that are localized to these inferior parietal regions (Heilman et al, 1982;Heilman and GonzalezRothi, 1993). A more recent voxel-based lesion-symptom mapping study in apraxic patients without aphasia suggested that the left inferior frontal gyrus rather than inferior parietal cortex is associated with deficits in gesture discrimination (Pazzaglia et al, 2008). Two lesion subtraction studies implicated a relatively extensive region containing inferior frontal as well inferior parietal cortex in gesture recognition (Tranel et al, 2003;Buxbaum et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Another fMRI study investigating brain activity during the observation of actions embedded or not embedded in contexts also confirmed the intention understanding function of the inferior frontal gyrus (Iacoboni et al., 2005b). Damage to the IFG has been shown to be associated with action understanding (e.g., gesture discrimination) deficits (Pazzaglia, Smania, Corato, & Aglioti, 2008). The role of the IFG in understanding action intention was confirmed by another study, which found that the activation in the IFG increased when the action intention is unusual (De Lange, Spronk, Willems, Toni, & Bekkering, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The data presented by Pazzaglia et al (2008) provide exciting evidence for a functional link between action observation and action execution in the human brain, the implications of which are widespread for both speech and limb apraxia. Furthermore, this provides a neurobiological rationale for established rehabilitation techniques and a framework for further development.…”
mentioning
confidence: 95%
“…In a recent study published in The Journal of Neuroscience, Pazzaglia et al (2008) demonstrate that patients with limb apraxia, a specific deficit in executing skilled limb movements or gestures, also display a deficit in recognizing observed gestures. This study expands on previous studies (Rothi et al, 1985;Cubelli et al, 2006) by including a more detailed lesion analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation